THE UNIQUENESS OF THE METHODOLOGY OF VOCAL AND CHORAL WORK IN MUSIC CULTURE LESSONS (Web of Teachers: Inderscience Research, 2025)
The uniqueness of the methodology of vocal and choral work in music culture lessons plays a pivotal role in shaping students' musical abilities and fostering a deeper appreciation for collective music-making. This approach integrates theoretical and practical knowledge, emphasizing the development of vocal techniques, choral harmony, and ensemble coordination. The study highlights the distinctive nature of this methodology by focusing on the pedagogical strategies employed in vocal and choral training, which encompass both individual and group instruction. These strategies aim to cultivate vocal skills, musical expression, and teamwork, enabling students to explore diverse musical genres and traditions. By analyzing the impact of choral work on the development of listening, timing, and artistic interpretation, this research underscores the value of vocal and choral practices in enhancing students' overall musical literacy.